Features of the Second Republic of Lithuania: the End of Culturati and the Rise of the Postmodern - Šaulauskas, Marius Povilas (Problemos, 1999)
Could the story of contemporary Lithuania, along with other post-communist countries, be written as a narration on a modern society that abruptly invaded the unexplored realities of the (post-modern) Plastic Can as contrasted with the (modern) Iron Cage? Is it the intrusion of the Postmodern, which constitutes the main source of problems she today encounters as well as the conceptual key to understand the ongoing transformations of the “unhandy” postcommunist habitat? If so, why, given the three traits of the “traditional” post-modern visage, Lithuanian postcommunist experience of the Plastic Can does cover aesthetic and cultural, but fundamentally lack conceptual intimation? And, most importantly, were the postcommunist revolutions determined by the moral-political activity of the Civil Society, including national culturati? Is it true that the postcommunist revolution was unfolded as a direct political activity of the Civil Society acting as a moral-cultural agent and, if so, what does it mean for the conceptual understanding of the postcommunist reality? And, more specifically, given the postmodern vista of moral politics backed by the revolutionary role of Civil Society. What is the socio-cultural configuration of the rise and actuality of contemporary Lithuanian habitat?